Non-greedy minimum interference routing algorithm for bandwidth-guaranteed flows - Tan, Su Wei; Lee, Sze Wei; Vaillaint, Benoit (Elsevier, 2002)
This paper presents a new non-greedy routing and admission control algorithm for the dynamic routing of bandwidth-guaranteed tunnels. The algorithm operates online that is handling requests which arrive one at a time without prior knowledge of the traffic pattern. It combines the key concepts in the minimum interference routing algorithm and the algorithms developed based on theoretic competitive analysis to provide efficient routing. Using extensive simulations, we show that our algorithm out-performs several previously proposed algorithms on several metrics such as the acceptance rate of the tunnel set-up requests, fairness and the capability of providing priorities to tunnel requests of certain source-destination pairs in the network. (C) 2002 Elsevier Science B.V. All rights reserved.